2019
DOI: 10.1136/bmjhci-2019-100007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the eCARE programme: a short message service for asthma monitoring

Abstract: ObjectiveTo evaluate the effectiveness of the upgraded eCARE monitoring system on asthma control in discharged emergency department (ED) patients.MethodsA multicentre randomised controlled study (randomised controlled trial) was done for patients with a primary diagnosis of asthma seen at the EDs in Singapore between 1 March 2013 and 28 February 2015. Those who met the inclusion criteria were randomised into a control group (routine care, n=212) and intervention group (eCARE, n=212). Patients in the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Of these, 5105 received telerehabilitation and 4572 received conventional face-to-face consultations; 6 studies were 3-armed randomized controlled trials [11][12][13][14][15][16], and the remaining studies were 2-armed studies. Among the 38 included studies, 9 targeted patients with cardiac disease [15][16][17][18][19][20][21][22][23], 9 targeted chronic patients with respiratory disease [24][25][26][27][28][29][30][31][32], 9 targeted patients with diabetes [11,12,[33][34][35][36][37][38][39], 4 targeted patients with hypertension [14,[40][41][42], 4 targeted patients with cancer [43][44][45][46], and 3 targeted patients with stroke [13,47,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 5105 received telerehabilitation and 4572 received conventional face-to-face consultations; 6 studies were 3-armed randomized controlled trials [11][12][13][14][15][16], and the remaining studies were 2-armed studies. Among the 38 included studies, 9 targeted patients with cardiac disease [15][16][17][18][19][20][21][22][23], 9 targeted chronic patients with respiratory disease [24][25][26][27][28][29][30][31][32], 9 targeted patients with diabetes [11,12,[33][34][35][36][37][38][39], 4 targeted patients with hypertension [14,[40][41][42], 4 targeted patients with cancer [43][44][45][46], and 3 targeted patients with stroke [13,47,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies integrated telemonitoring in their telerehabilitation program for patients with heart failure, asthma, COPD, or diabetes [16,18,21,[29][30][31][32]34,35] (Multimedia Appendix 4). Patients were instructed to measure their disease-specific physical indicators (eg, blood pressure, spirometry, oxygen saturation, respiratory rate, blood glucose level) and record their signs and symptoms daily (n=5), weekly (n=1), or from daily to weekly after the first few weeks of interventions (n=3).…”
Section: Telemonitoringmentioning
confidence: 99%
“…A systematic review and meta-analysis of 21 studies on the use of Asthma Control Test (ACT) and Asthma Control Questionnaire (ACQ) for assessing asthma control (11,141 subjects for ACT and 12,483 assessed for ACQ) indicated that ACT had good accuracy for assessment of controlled and not well-controlled asthma, and the ACQ had good diagnostic accuracy for assessment of not well-controlled asthma. 22 However, neither were as accurate for the assessment of uncontrolled asthma.…”
Section: Statement 4 (Consensus Level 94%)mentioning
confidence: 99%
“…8 Although the value of each domain is appreciated, only a limited number of studies have directly assessed the effectiveness of different monitoring strategies or tools in improving asthma control and reducing exacerbations, and these have had conflicting results across different asthma-related outcomes. [9][10][11] Therefore, it is evident that prioritization of monitoring approaches, determination of frequency and intensity of implementation, and recommendations for incorporation into care pathways in different populations and healthcare levels are essential.…”
Section: Introductionmentioning
confidence: 99%
“…As this challenge is not unique to AIT but holds true for most chronic diseases requiring continuous medication intake, several strategies for digital support have been proposed. From relatively simple reminder systems [ 40 ], to more complex models including efficacy feedback [ 41 , 42 ] and the use of artificial intelligence [ 43 ], a broad variety of tools has been developed and partly also evaluated in clinical studies with diverse results [ 44 ]. A commonly described challenge for digital support technologies is the fact, that one tool does not fit all patients, but the choice of support should ideally be based on individual needs and preferences.…”
Section: Ehealth For Ait Managementmentioning
confidence: 99%